Effects of peer learning on nursing students' learning outcomes in electrocardiogram education. (January 2022) - Ko, Youngmin; Issenberg, S. Barry; Roh, Young Sook
Abstract: Background: Nurses should have the ability to interpret electrocardiograms (ECGs) quickly and accurately, but their ECG interpretation skills may be suboptimal. The best evidence for effective teaching methods is lacking. Objectives: This study aimed to compare the effects of peer and self-directed individual learning methods on nursing students' learning flow, interpretation skills, and self-confidence in web-based ECG education. Design: This study employed a nonequivalent control group with a pretest-posttest design. Settings. This study was conducted at two colleges of nursing in the Republic of Korea. Participants: Nursing students were conveniently assigned to either a peer learning group ( n = 45) or a self-directed individual learning group ( n = 51). Methods: A self-administered questionnaire was used to measure the nursing students' learning flow and self-confidence in ECG rhythm interpretation. ECG interpretation skills were measured using a web-based interpretation skills test. Data were analyzed using a paired t -test and a two-sample t-test. Results: Nursing students in both groups showed improved learning flow, interpretation skills, and self-confidence after ECG education compared with before learning. However, there were no significant pretest-posttest differences in learning flow, interpretation skills, or self-confidence between the two groups. Conclusions: Peer learning was as effective as self-directed individual learning in improving nursing students' learning flow, interpretations skills, and self-confidence in web-based education. Nurse educators should educate nursing students to have optimal ECG interpretation abilities, and web-based peer or individual learning are effective education methods. Highlights: Education is needed to improve nurses' ECG interpretation competency. Peer learning was as effective as individual learning in improving learning flow, skills, and self-confidence. Web-based peer or individual learning can be effective strategies for ECG education.